The Existential Crisis in the Novel Lho: An Existential Psychological Analysis Based on Rollo May’s Perspective - Dianatul Ilmi; Misbahus Surur; Khafid Roziki (Jurnal Sastra Indonesia, 2025)
This study examines the existential crisis of the main character in Putu Wijaya's novel Lho using Rollo May's existential psychology theory. The primary aim of this research is to analyze the concepts of being-in-the-world (existence) and non-being (non-existence) in the life journey of the main character. This research employs a descriptive qualitative method, with data consisting of the main character's dialogues and monologues. The findings reveal that the concept of being-in-the-world is represented through three dimensions: (1) the character's relationship with the physical environment (Umwelt), (2) the character's relationship with others (Mitwelt), and (3) the character's relationship with themselves (Eigenwelt). Meanwhile, the concept of nonbeing is represented through: (1) fear of consequences, (2) a crisis of trust, and (3) destructive behavior. These findings do not function merely as adverse conditions but as forces that shape the character’s efforts to negotiate meaning and existence. This study aims to provide a deeper understanding of how the concepts of being-in-the-world and non-being can be applied to explain individual existential crises in literary studies, as well as in broader human experiences.